Fantastic confabulation in right frontal lobe epilepsy - Fujikawa, Mayu (Epilepsy Behav Case Rep, 2016)
BACKGROUND: Interictal behavioral symptoms in frontal lobe epilepsy (FLE) are variable and often difficult to discriminate from other localization-related epilepsies. METHODS AND RESULTS: We report two female patients with right FLE who exhibited fantastic confabulations. One of the patients had a 14-year history of hypermotor seizures, and the other had a 10-year history of dyscognitive seizures with automatism. Their fantastic confabulations arose in the context of moderate-to-severe cognitive impairment and of a variety of behavioral abnormalities, including emotional withdrawal and compulsive behaviors. CONCLUSION: Fantastic confabulations are rare but may be a relatively specific behavioral marker for FLE-associated psychosis.